INSEMINASI DAN BAYI TABUNG - Abdul Wahab Syakhrani; Rahniatul Jannah, Raudatunnisa, Risa Amelia, Sapiah (CV. Adiba Aisha Amira, 2024)
Artificial insemination or IVF means a method to help fertile couples who experience difficulties in fertilizing a woman's egg cells by a man's sperm cells. To carry out artificial insemination (al-talqih al-Sina'iyah), a husband and wife who want to get pregnant are expected to always consult a doctor as to whether they can inseminate/be fertilized to produce offspring or not. Many people actually have sperm or ovum that is quite fertile, but cannot fertilize or be fertilized because there are abnormalities in their reproductive organs, for example the Fallopian Tubes are narrowed or the sperm emission is always weak, so this will hinder birth. If a case like this occurs, the doctor will try to take the woman's eggs (ovum) by means of aspiration of follicular fluid through the vagina, with a tool called